THE EFFECT OF LIQUIDITY, LEVERAGE, AND BOPO ON PROFITABILITY IN ENERGY SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) DURING HE 2022–2024 PERIOD - Maulidia, Chentia; Jufri, Ali; Sylvani, Sylvani (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the effects of liquidity, leverage, and BOPO on the profitability of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Profitability is proxied by Return on Assets (ROA), liquidity by the Current Ratio (CR), leverage by the Debt to Equity Ratio (DER), and BOPO is measured by the ratio of Operating Expenses to Operating Income. This research employs a quantitative approach with an associative research design. The data used are secondary data in the form of companies’ annual financial statements obtained from the official IDX website, with the sampling technique using purposive sampling based on predetermined criteria. Data analysis was conducted using multiple linear regression with the assistance of statistical software. The results show that liquidity does not always have a positive effect on profitability, leverage tends to have a negative effect on profitability, and BOPO has a negative effect on profitability. Simultaneously, liquidity, leverage, and BOPO significantly affect the profitability of energy sector companies during the 2022–2024 period. These findings indicate that optimal liquidity management, proportional use of debt, and operational cost efficiency are key factors in improving the profitability performance of energy sector companies.